Systems biology applied to the study of papaya fruit ripening: the influence of ethylene - Soares, Caroline Giacomelli (2021)
Fruit ripening is a biochemical process that results in flavor, odor, texture, and color suitable for human consumption, in addition to providing access to important nutrients. Although ripening promotes sensory and nutritional increases in fruits, there is also an increased susceptibility to physical damage, as is the case with papaya. These transformations occur due to changes in gene expression patterns at different stages of maturity, whose control and coordination result from the combined action of plant hormones, especially ethylene. As the action of this hormone in the regulation of gene expression is still elusive, this dissertation sought to address the global analysis of the transcriptome in an overview study of molecular processes involved in the ripening of ethylene-treated and non-treated papaya. Transcription factors related to ethylene synthesis and signaling had increased activity towards exogenous-ethylene treatment. Consequently, ethylene-induced enzymes had their coding genes differentially expressed, like genes related to the synthesis of carotenoids, linalool, and vitamins, which increase color, aroma, and antioxidant activity, respectively. Metabolic pathways related to the synthesis of sugars were suppressed while genes encoding the enzyme responsible for sucrose synthesis maintained a basal expression, showing that the accumulation of sugars occurs before the ripening process. The firmness of the peel and pulp of the fruits were strongly influenced by the treatment with ethylene and by the time of the experiment, suffering the action of numerous enzymes related to the degradation of the cell wall. The main enzyme responsible for softening the pulp was polygalacturonase, together with the activity of other pectinases and cellulases. In contrast to the need for the pre-climacteric action of pectate lyase and pectinesterase reported in other fleshy fruits, such as tomatoes and strawberries, papaya did not show a significant difference in their expression. The meta-analysis of several papaya ripening transcriptomes confirmed the expression profile observed in the previous RNA-seq, besides providing statistical enrichment to the biological narratives. Finally, the present study gathered a range of robust information on the gene regulation of the papaya ripening process, which opens possibilities for future approaches to transcriptomic analysis and validates the use of papaya as a model for such studies.